Unraveling the key drivers of bacterial progesterone degradation - Gabriel Hernández-Fernández; Juan Ibero; José L. García; Beatriz Galán (mBio)
ABSTRACT Progesterone (PROG) is one of the most ubiquitous sexual hormones found as a pollutant in soil and water systems. Despite the fact that PROG can be degraded by various bacterial species, the pathways leading to its complete oxic mineralization remain unknown. In this study, we investigated bacterial progesterone catabolism using the steroid-degrading bacterium Caenibius tardaugens as a model, in which we demonstrated its capacity to degrade progestogens. The transcriptomic analyses in the presence of PROG showed the overexpression of EGO55_13845 and EGO55_13860 genes, coding a Baeyer-Villiger monooxygenase (BVMO) and a luciferase-like monooxygenase (LLM), respectively. Both genes are located next to two regulatory proteins forming a small gene cluster (named pdc) that can be found in other steroid-degrading bacteria. Mutagenic analyses and gene complementation allowed ascertaining that EGO55_13845 and EGO55_13860 genes are involved in PROG degradation. To assess their enzymatic activities, both proteins were overexpressed in Escherichia coli, showing that they catalyze a Baeyer-Villiger monooxygenation of PROG, resulting in the production of testosterone acetate. They are also active on 1,2-dehydroprogesterone, an intermediate in PROG degradation, converting it into boldenone acetate. BVMO and LLM enzymes are functionally redundant, as each can replace the other in metabolizing PROG. The presence of two functionally redundant BVMO and LLM enzymes in C. tardaugens can be explained by their distinct substrate preferences. Our results settle for the first time the genetic and biochemical basis for explaining how PROG is recognized and channeled into the 9,10-seco degradation pathway in a PROG-degrading bacterium.IMPORTANCEThis study investigates for the first time the key steps in bacterial progesterone (PROG) degradation, revealing new insights into the process. The main stages of PROG degradation were examined in the bacterium Caenibius tardaugens. The conducted transcriptomic analysis allows identifying the progesterone degradation cluster pdc, which is also present in other related bacteria. We demonstrated that Baeyer-Villiger monooxygenase and luciferase-like monooxygenase encoded within the pdc cluster catalyze the PROG Baeyer-Villiger monooxygenation, producing testosterone acetate. The activity redundancy can be explained by the difference in substrate specificity of each enzyme.